Sistem Pemantauan Kinerja Petugas Pengantar Tagihan Listrik pada PT PLN ULP Nabire kota Berbasis Web - Agung Hardiansyah; Kristia Yuliawan (STMIK Pesat Nabire, 2025)
Efficient operations of PT PLN, as a vital electricity provider, heavily rely on effective service management, including customer data collection and payment processing. Employee performance supervision is crucial to ensure optimal results and customer satisfaction, given that traditional manual systems often suffer from inefficiencies, inaccuracies, and delays. This research aims to develop and implement a web-based performance monitoring system for electricity bill delivery officers to enhance operational efficiency and accountability at PT PLN. The Waterfall method was adopted as a systematic development framework, encompassing stages of requirements analysis, design using Unified Modeling Language (UML) such as use case diagrams and activity diagrams, implementation with PHP and MySQL, and black box testing to validate system functionality. The results of the black box testing indicate that all main functions of the system, including user authentication, user data management, uploading of daily reports and supporting files by officers, and the administrator's ability to monitor and review reports, function as expected. The successful implementation of this system indicates its capability to overcome the limitations of manual methods and provide real-time visibility into the performance of field officers. Thus, this web-based monitoring system not only contributes to improving data accuracy and operational efficiency at PT PLN but also supports more informative and strategic managerial decision-making, aligning with digital transformation initiatives in the energy sector